Pythagorean Fuzzy Small Submodules (European Journal of Pure and Applied Mathematics, 2022)
In this paper, we introduce the notion of a pythagorean fuzzy small submodule. We prove various characterisations for pythagorean fuzzy small submodules. We provide a relation between a pythagorean fuzzy small submodule and a basic small submodule. In addition, some important properties regarding pythagorean fuzzy small submodules are investigated.
Keywords: pythagorean fuzzy set; pythagorean fuzzy small submodule; homomorphism